2015
DOI: 10.3109/0284186x.2015.1064161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of miR-21 and miR-375 as prognostic biomarkers in esophageal cancer

Abstract: Background. MicroRNAs (miRNAs) have been associated with prognosis in esophageal cancer, suggesting a role for miRNAs to help guide treatment decisions. Especially, miR-21 and miR-375 have been investigated as prognostic biomarkers. The aim of this study was to evaluate the prognostic potential of miR-21 and miR-375 in primary esophageal squamous cell carcinomas (ESCC) and esophagogastric adenocarcinomas (EAC). Material and methods. Pre-therapeutic tumor specimens from 195 patients with loco-regional esophagea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…miRNA (miR)-375 may function as a tumor suppressor, and there is increasing evidence to suggest that it may be useful as a diagnostic biomarker and a therapeutic target for cancer treatment. Winther et al (7) demonstrated that miR-375 served as a prognostic biomarker in patients with primary esophageal squamous cell carcinomas. In laryngeal squamous cell carcinoma, the miR-21/miR-375 ratio was revealed as an independent prognostic marker (8).…”
Section: Introductionmentioning
confidence: 99%
“…miRNA (miR)-375 may function as a tumor suppressor, and there is increasing evidence to suggest that it may be useful as a diagnostic biomarker and a therapeutic target for cancer treatment. Winther et al (7) demonstrated that miR-375 served as a prognostic biomarker in patients with primary esophageal squamous cell carcinomas. In laryngeal squamous cell carcinoma, the miR-21/miR-375 ratio was revealed as an independent prognostic marker (8).…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic model for EC has been continuously updated [25][26][27]. In this study, we identi ed 247 up-regulated and 56 down-regulated IRGs in EC and screened out survival-related IRGs.…”
Section: Discussionmentioning
confidence: 99%
“…The facts that various miRNAs are strikingly deregulated in many kinds of cancer cells under hypoxia stress strongly suggests that they may play important roles in cancer development. [45][46][47][48] However, the precise roles of miRNAs in hepatocellular carcinoma development under hypoxia stress are far from clear. In the present study, we performed a high-throughput RNA sequencing to identify miRNAs in HepG2 cells response to the hypoxia treatment and performed an integrative analysis of their target genes and dynamic of biological process, which provides deeper insight into the expression proles of miRNAs in HepG2 cells under hypoxia stress.…”
Section: Discussionmentioning
confidence: 99%